ETIKA KOMUNIKASI MEDIA SOSIAL FACEBOOK (STUDI EKSPLORASI TERHADAP TINDAKAN BULLYING BAGI MAHASISWA FAKULTAS ILMU SOSIAL DAN ILMU PEMERINTAHAN UNIVERSITAS AL ASYARIAH MANDAR) - Muhammad Syaeba (MITZAL (Demokrasi, Komunikasi dan Budaya) : Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2016)
This study discusses ethics in a communication process that takes place in virtual public space through social media. A search of the behavior and actions of bullying on Facebook media, both as perpetrators and as victims whose subjects are students of the Faculty of Social Sciences and Government of Al Asyariyah Mandar University. Facebook media is very free and ethical issues depend on the individual users. By that, Facebook media has very good benefits and also has a negative impact on ethical principles. Bullying attitudes and actions have more psychological dimensions, carried out with various motivations, for example; angry and wants revenge, frustration, looking for attention, just entertainment time, or just joking.